Collocations in written expression by Arabic learners in Nigeria - Abubakar, Mahmud Garba (2024)
expression. However, undergraduate learners of Arabic language at the Department of Arabic Language, Umaru Musa Yar’adua University, Katsina, Nigeria, encounter numerous problems in producing a well-constructed written expression, especially when writing essays, as they are unable to select the right words and arrange them in sentences in an order that is acceptable to those who speak Arabic. This leads to the problem of linguistic overlap and ambiguity of meaning in certain constructions due to the violation of the Arabic language system because of incompetence in the use of collocations in written expression. Therefore, the objectives of the study are to examine the contribution of collocations in facilitating the learning and development of Arabic vocabulary among the undergraduate learners of Arabic at the Department of Arabic Language, Umaru Musa Yar’Adua University, Katsina, Nigeria. In addition, the study also aims to analyse the impact of collocations on the development and enhancement of written expression among these students in terms of content, use of collocations and their significance in language use. In addition, the study deals with the organisation of written expression in the form of essay writing. In addition, the study evaluates and observes students' perceptions and experiences of their background in learning vocabulary in the form of collocations and their role in minimising linguistic errors. Finally, students' experiences in improving written expression using collocations will also be examined. The study employed a quasi-experimental method with a two-group design. The sample of the study comprised an intact class of seventy (70) third year undergraduate students enrolled in the essay writing course at the Department of Arabic Language who were then divided into the experimental group (n = 35) and the control group (n = 35). The researcher conducted a twelve-week training in the academic year 2022- 2023. Therefore, the lexical approach theory, a well-known theory of foreign language learning, the cognitive theory of writing, and McCarthy and O'Dell's (2005) model for the stages of collocation learning were combined to achieve the objectives of the study. The study employed a collocation test, an essay writing test in the pre- and post-tests and the questionnaire at the end of the training as tools for data collection. Finally, the researcher conducted an inferential analysis by performing paired-samples t-tests and independent-samples t-tests focusing on the content of writing, use of collocations, language use and organisation of writing to find a significant difference between the two groups which enabled him to make a final decision on the effect of the treatment of the experimental group. The study showed that the performance of the experimental group improved compared to the control group in the posttest in terms of writing content, use of vocabulary in the form of collocations, language use and organisation compared to the pretest. The results indicated a statistically significant difference at the significance level below.05 (p = 000) between the two groups, demonstrating the role of collocations in improving the participants' writing skills. It can therefore be concluded that collocations have an impact on the development and improvement of written expression in the form of essay writing for undergraduate learners of Arabic as a foreign language in Nigeria.